Migrant labor markets and the welfare of rural households in the developing world: Evidence from China - Alan De Brauw; John T. Giles (Institute for the Study of Labor (IZA), 2012)
In this paper, we examine the impact of reductions in barriers to migration on the consumption of households in rural China. We find that increased migration from rural villages leads to significant increases in consumption per capita, and that this effect is stronger for poorer households within villages. Household income per capita and non-durable consumption per capita both increase with out-migration, and this increase is greater for poorer households. We also establish a causal relationship between increased out-migration and investment in housing and durable goods assets, and these effects are also stronger for poorer households. We do not find robust evidence, however, to support a connection between increased migration and investment in productive activity. Instead, increased migration is associated with two significant changes for poorer households: increases both in the total labor supplied to productive activities and in the land per capita managed by the household. In examining the effect of migration, we pay considerable attention to motivating, developing and evaluating our identification strategy.
Keywords: O12; O15; J22; J24; 330; migration; migrant networks; consumption; poverty; wealth; rural China; Landflucht; Ländlicher Arbeitsmarkt; Landbevölkerung; Verbraucherausgaben; China